2022
DOI: 10.1007/s40964-022-00281-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of energy density and porosity structure on tensile properties of 316L stainless steel produced by laser powder bed fusion

Abstract: Understanding the influence of process parameters and defect structure on the properties of parts produced via laser powder bed fusion (L-PBF) is a fundamental step towards the broader use of additive manufacturing technologies in critical applications. Furthermore, the ability to predict mechanical properties by simply considering information on the process parameters and defects observed via X-ray computer tomography (XCT) allows one to avoid expensive destructive testing, provide an in-depth understanding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that laser power, hatching space, and scanning speed affect the density, and thus, the study of a single variable is not accurate [29,30]. Most studies have attributed the factors to the volume-based energy density E [31][32][33][34][35]. Similar to other studies, LOF defects occurred when E was insufficient, and keyhole defects appeared when E was too high.…”
Section: Mpl Model and Parameter Optimizationmentioning
confidence: 71%
“…Previous studies have shown that laser power, hatching space, and scanning speed affect the density, and thus, the study of a single variable is not accurate [29,30]. Most studies have attributed the factors to the volume-based energy density E [31][32][33][34][35]. Similar to other studies, LOF defects occurred when E was insufficient, and keyhole defects appeared when E was too high.…”
Section: Mpl Model and Parameter Optimizationmentioning
confidence: 71%
“…On the other hand, if the energy is too high, keyhole porosity defects can occur. 33,34 Lack of fusion defects are identified by the unmelted powders and can be aligned perpendicular to (lack of fusion between layers) or parallel to the building direction (lack of fusion between scan tracks). According to Yang et al, 11 irregularly shaped defects with unmelted regions are sometimes aligned either perpendicular or parallel to the building direction due to a lack of fusion.…”
Section: Introductionmentioning
confidence: 99%
“…If the energy density is insufficient, lack of fusion defects may form. On the other hand, if the energy is too high, keyhole porosity defects can occur 33,34 …”
Section: Introductionmentioning
confidence: 99%
“…This equation takes the assumption that the melt pool is in the liquid phase until the next hatch. can be related to part quality since low energy levels result in a lack of fusion porosity, meaning that the energy is not sufficiently melting the powder, causing large, irregular porosities throughout the part [27], [28]. Conversely, at higher energy levels, a phenomenon called balling can occur.…”
mentioning
confidence: 99%
“…Conversely, at higher energy levels, a phenomenon called balling can occur. Moreover, when surface tension forces overcome a mixture of dynamic fluid, gravitational, and adhesion forces, a ball of molten metal will form [11], [27], [29], [30]. Therefore, it can be understood how part quality can be determined via energy density.…”
mentioning
confidence: 99%